A chromatin signature by the methyltransferase SETD7 regulates semaphorin-3G transcription and angiogenic response in diabetes: insights for personalized epigenetic therapies. (25th November 2020) - Mohammed, S.A; Costantino, S; Akhmedov, A; Karsai, G; Ambrosini, S; Spinetti, G; Madeddu, P; Luscher, T.F; Paneni, F
Abstract: Background: Despite advances in revascularization strategies, type 2 diabetic (T2D) patients with peripheral artery disease (PAD) continue to have a high risk of limb amputation. Modulation of blood vessel growth holds great promise for the treatment of PAD patients. Epigenetic modifications, namely histone post-translational modifications, have shown to regulate transcriptional programs implicated in the pathogenesis of cardiovascular disease. Aim: To investigate the role of chromatin changes in regulating post-ischemic vascularization in experimental diabetes as well as in patients with T2D. Methods: Experiments were performed in primary human aortic endothelial cells (HAECs), double-mutant leptin deficient mice (Lepdb/db) carrying a genetic deletion of the methyltransferase SETD7 (Setd7−/−Lepdb/db) as well as in gastrocnemius muscle samples from T2D patients with PAD and age-matched non-diabetic controls. Unbiased gene expression profiling was performed by RNA sequencing (RNA-seq) followed by Ingenuity Pathway Analysis (IPA). Pharmacological blockade of SETD7 was performed by using the selective inhibitor (R)-PFI-2. Scratch and tube formation assays were performed to investigate the impact of SETD7 on angiogenic response. Results: RNA-seq in high glucose-treated HAECs revealed a profound upregulation of the methyltransferase SETD7 (fold change 2.8, p<0.001), an enzyme involved in mono-methylation of lysine 4 at histone 3 (H3K4me1). Both SETD7 gene silencing and pharmacological inhibition by (R)PFI-2 rescued hyperglycemia-induced impairment of HAECs migration and tube formation, while SETD7 overexpression blunted the angiogenic response. RNA-seq and Chromatin Immunoprecipitation (ChIP) assays showed that SETD7-dependent H3K4me1 regulates the transcription of the angiogenesis inhibitor semaphorin-3G (SEMA-3G). Increased SEMA-3G transcript was associated with enhanced secretion from HAECs. Co-immunofluorescence experiments showed that SEMA-3G blunts the angiogenic response by competing with VEGF receptors VEGFR/Neuropillin2. Moreover, SEMA-3G overexpression blunted migration and tube formation in SETD7-depleted HAECs. SETD7 and SEMA-3G were significantly upregulated in endothelial cells from Lepdb/db mice, whereas SEMA-3G transcription was blunted in Setd7−/−Lepdb/db animals. Consistently, endothelial sprouting was defective in aortas from Lepdb/db as compared to WT mice, whereas Setd7−/−Lepdb/db mice displayed a preserved angiogenic response. Of clinical relevance, SETD7/SEMA-3G axis was upregulated in gastrocnemius muscle specimens from T2D patients with PAD as compared with non-diabetic controls. Conclusion: In HAECs, genetically modified mice and T2D patients we show that SETD7-dependent chromatin changes regulate SEMA-3G transcription and angiogenic response. Pharmacological inhibition of SETD7 may represent a novel epigenetic therapy to boost neovascularization in T2D patients with PAD. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): University of Zurich/Universitätsspital Zürich